Breast-Volume Displacement Using an Extended Glandular Flap for Small Dense Breasts. (20th September 2011) - Ogawa, Tomoko; Hanamura, Noriko; Yamashita, Masako; Kimura, Hiroko; Kashikura, Yumi
Abstract : We defined the glandular flap including fat in the subclavicular area as an extended glandular flap, which has been used for breast-conserving reconstruction in the upper portion of the breast. Indication . The excision volume was 20% to 40% of the breast volume, and the breast density was dense. Surgical Technique. The upper edge of the breast at the subclavicular area was drawn in the standing position before surgery. After partial mastectomy, an extended glandular flap was made by freeing the breast from both the skin and the pectoralis fascia up to the preoperative marking in the subclavicular area. It is important to keep the perforators of the internal mammary artery and/or the branches of the lateral thoracic artery intact while making the flap. Results . Seventeen patients underwent remodeling using an extended glandular flap. The cosmetic results at 1 year after the operation: excellent in 11, good in 1, fair in 3, and poor in 2. All cases of unacceptable outcome except one were cases with complications, and more than 30% resection of moderate or large size breasts did not obtain an excellent result for long-term followup. Conclusion . This technique is useful for performing the breast-conserving reconstruction of small dense breasts.